1997
DOI: 10.1002/(sici)1096-987x(199709)18:12<1496::aid-jcc7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Coupled semiempirical molecular orbital and molecular mechanics model (QM/MM) for organic molecules in aqueous solution

Abstract: A coupled quantum mechanical and molecular mechanical (QM/MM) model based on the AM1, MNDO, and PM3 semiempirical molecular orbital methods and the TIP3P molecular mechanics model for liquid water is presented. The model was parameterized for each of the three molecular orbital methods using the aqueous solvation free energies of a wide range of neutral organic molecules, many of which are representative of amino acid side chains. The fit to the experimental solvation free energies was achieved by varying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 52 publications
1
65
0
Order By: Relevance
“…We recently reported results of both quantum chemical calculations and MD simulations within a QM/MM scheme for both the substrate and activesite residue protonations. [9][10][11] These studies demonstrated the importance of the conserved water molecule, corresponding to W206 in the E. coli DHFR complexes (Figure 1), and also suggested that the issue of OD2 protonation is likely to be important mechanistically. 11 Overall, these results tended to support a mechanism for both folate and DHF reductions in which the OD2 carboxyl oxygen is first protonated, followed by a direct protonation at N8 (folate) or N5 (DHF) to obtain the doubly protonated active cation complexes.…”
Section: Introductionmentioning
confidence: 84%
“…We recently reported results of both quantum chemical calculations and MD simulations within a QM/MM scheme for both the substrate and activesite residue protonations. [9][10][11] These studies demonstrated the importance of the conserved water molecule, corresponding to W206 in the E. coli DHFR complexes (Figure 1), and also suggested that the issue of OD2 protonation is likely to be important mechanistically. 11 Overall, these results tended to support a mechanism for both folate and DHF reductions in which the OD2 carboxyl oxygen is first protonated, followed by a direct protonation at N8 (folate) or N5 (DHF) to obtain the doubly protonated active cation complexes.…”
Section: Introductionmentioning
confidence: 84%
“…Only this approach suggests a consistent prescription for separating the inertial response field component at a molecular level. 43,44 Several other combined ͑hybrid͒ methods were suggested in the literature and, with a relevant parametrization, successfully used for the computation of hydration free energies of organic molecules 26,30,[45][46][47][48] and polyatomic ions. 25,27,30,31,49 All these methods are inapplicable for separating the inertial response.…”
Section: Discussionmentioning
confidence: 99%
“…The basic approach is to treat the chemically most relevant region by quantum mechanics, whereas the rest of the system is treated by classical molecular a͒ Author to whom all correspondence should be addressed; electronic mail: bernd.m.rode@uibk.ac.at mechanics. [33][34][35][36][37][38][39][40][41] Such ab initio QM/MM molecular dynamics have been successfully employed for revealing structural and dynamic properties of various ions in solution. [42][43][44][45][46][47][48][49] In the present work the same way has been followed for the investigation of Hg 2ϩ , which in contrast to previously investigated metal ions represents the rather ''heavy'' elements and, therefore, also displays a quite different chemical behavior.…”
Section: Introductionmentioning
confidence: 99%